Pengaruh Motivasi, Sarana Dan Prasarana,Tanggungjawab Dan Kompensasi Terhadap Kinerja Pegawai Dinas Perhubungan Kabupaten Gowa - Mustari; Natsir, Muhammad; Syam, Andi Hendra (STIM-LPI Makassar, 2024)
This research carried out from March to Ausgut 2023 with research location at Regional Gowa District Transportation Department. The aim of this research is (1) to know the influence of motivation, facility, and infrastructure, responsibility and compensation towards the erformance of Gowa District Transportation Department; (2) to know some dominant factors influencing the staff performance of Gowa District Transportation Department. This research is a survey towards the staff of Gowa District Transportation Department with analysis unit in this research is individual. Sample selection is by using total sampling method. The observed variable is (1)staff performance (2) motivation (3)facility and infrastructure, (4) responsibility, and (5) compensation. The obtained data then analyzed by using double regression with calculation through computer with program SPSS 12.00. The results show that (1) motivation factor, facility and infrastructure, and conpensation show that simultanously four variables give positive and significant influence towards the improvement of staff performance at Gowa District Transportation Department, (2) the results of analysis with double regression show that motivation factors is variable that mostly give contribution towards the improvement of staff performance at Gowa District Transportation Department. This results supported by high motivation of staff namely (67%).